TUNA SUPPLY CHAIN RISK ANALYSIS IN THE BANDA NEIRA ISLANDS - Sahar, Dian Pratiwi; Afifudin, Mohammad Thezar (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2025)
The Banda Sea waters contribute significantly to tuna production in Maluku. The fishing community of the Banda Neira Islands uses this zone as their main source of income. This significant contribution needs to be supported by development efforts through research and innovation. Until now, research on the tuna supply chain from the Banda Neira archipelago is particularly rare. This research seeks to provide comprehensive, micro-level information on the mapping of tuna supply chain risks in Indonesia, particularly in Maluku, that has been reviewed by several researchers. Several supply chain risk management (SCRM) methods, including 5-why analysis, supply chain risk identification (SCRI), and house of risk (HOR), were used in this study. The results indicate that the actors involved in the Banda Neira tuna supply chain include fishermen, cold storage, ship plan, and miniplan. Fishermen play a role in fishing operations, while cold storage, ship plan, and miniplan serve as buyers, processors, and ship plans/distributors to other regions. In the tuna supply chain, 11 risk events were identified, caused by 23 risk agents/factors. The two highest-ranking factors, in order of highest risk, were the lack of ice availability and high operational costs. Both factors had a cumulative percentage ratio of aggregate risk potential reaching 55.33%. This indicates that the tuna supply chain in the Banda Neira is still influenced by the performance of fishing operations (fishermen). To mitigate the 11 risk events, 22 preventive measures/actions are required.